The impact of abandoned iron ore on the endophytic bacterial communities and functions in the root systems of three major crops in the local area - Chen, Shuyi; Tang, Jie; Xu, Junqiang; Peng, Lianxin; Wu, Peng; Li, Qiang (Frontiers in Microbiology, 2025)
IntroductionGlobal mining activities have significant impacts on ecosystems, but most studies have focused only on the relationship between soil physicochemical properties and microbial diversity in soils. The present study provides an insight into the effects of mining activities on soil physico-chemical properties and endophytic bacterial community composition in the rhizosphere of three different crops.MethodsMusa basjoo Siebold L., Amygdalus persica L., and Triticum aestivum L. were collected from the inter-root soils and plant roots to determine the soil physicochemical properties and endophytic bacterial communities in the root system.ResultsThe results showed that mining resulted in soil acidification, altered trace element content and increased organic carbon. There was an increase in the Ascomycota and Actinobacteria phylum of crop root bacteria. Interestingly, the chao1 and shannon indices of the root endophytes of the mining crop were significantly elevated compared to the contro (p < 0.05). Among them, Musa basjoo Siebold showed the highest level of community richness in the mining environment. The mining environment resulted in functional enrichment of histidine kinases and oxidoreductases in the bacterial community. The total potassium (TK) content in the soil, as well as the Fe and Pb content, were positively correlated with the α-diversity index and Streptomyces. Zn and Ti content were significantly negatively correlated with the α-diversity index.DiscussionThis study provides data support for exploring the mechanisms of plant response to the mining environment and developing ecological restoration strategies for mining areas.